2016
DOI: 10.5194/angeo-34-927-2016
|View full text |Cite
|
Sign up to set email alerts
|

Observational evidence for new instabilities in the midlatitude <i>E</i> and <i>F</i> region

Abstract: Abstract. Radar observations of the E-and F -region ionosphere from the Arecibo Observatory made during moderately disturbed conditions are presented. The observations indicate the presence of patchy sporadic E (E s ) layers, medium-scale traveling ionospheric disturbances (MSTIDs), and depletion plumes associated with spread F conditions. New analysis techniques are applied to the dataset to infer the vector plasma drifts in the F region as well as vector neutral wind and temperature profiles in the E region.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…The observations support the theory with regard to the phase relationship between the MSTIDs and E s , suggesting that the MSTIDs and the plasma density irregularities of the E s layer were electrically coupled through the geomagnetic field line as predicted by the F ‐ F coupling instability theory (Cosgrove & Tsunoda, , ; Yokoyama et al, ). Such direct coupling between the plasma density irregularities of the E s layer and the MSTIDs in the F region could not be revealed by the E region and F region observations from a single site (Hysell et al, ).…”
Section: Resultsmentioning
confidence: 91%
“…The observations support the theory with regard to the phase relationship between the MSTIDs and E s , suggesting that the MSTIDs and the plasma density irregularities of the E s layer were electrically coupled through the geomagnetic field line as predicted by the F ‐ F coupling instability theory (Cosgrove & Tsunoda, , ; Yokoyama et al, ). Such direct coupling between the plasma density irregularities of the E s layer and the MSTIDs in the F region could not be revealed by the E region and F region observations from a single site (Hysell et al, ).…”
Section: Resultsmentioning
confidence: 91%
“…It has also been linked by numerous investigators to a particular plasma instability mechanism thought to operate at middle latitudes attributed to Perkins 27 . Mid-latitude spread F has furthermore been associated with patchy E s layers, observationally and theoretically, although different perspectives exist regarding the causal relationship 28 – 32 . Meter-scale irregularities in the F region are also known to cause coherent scatter 33 , 34 .…”
Section: Introductionmentioning
confidence: 99%
“…They are thought to be directly driven by GWs or result from the Perkins instability, which can be seeded by GWs (Behnke, ; Perkins, ; Shiokawa et al, ). Plasma perturbations due to MSTIDs may create conditions favorable for MSF formation via convective instabilities such as the Perkins instability (Hysell et al, ), although Shiokawa et al () reported MSF coincident with MSTIDs only 10–15% of the time.…”
Section: Introductionmentioning
confidence: 99%